The genetics and hormonal basis of human gender identity - Rafael Loch Batista; Luciana Mattos Barros Oliveira (Archives of Endocrinology and Metabolism)
ABSTRACT Gender identity refers to one's psychological sense of their own gender. Establishing gender identity is a complex phenomenon, and the diversity of gender expression challenges simplistic or unified explanations. For this reason, the extent to which it is determined by nature (biological) or nurture (social) is still debatable. The biological basis of gender identity cannot be modeled in animals and is best studied in people who identify with a gender that is different from the sex of their genitals such as transgender people and people with disorders/differences of sex development. Numerous research studies have delved into unraveling the intricate interplay of hormonal, neuroanatomic/neurofunctional, and genetic factors in the complex development of core gender identity. In this review, we explore and consolidate existing research that provides insights into the biological foundations of gender identity, enhancing our understanding of this intriguing human psychological trait.